Evaluación del proceso de pirólisis como alternativa de valorización para la rebaba de caucho en Croydon Colombia S.A. (2019)
The present work seeks to evaluate the process of pyrolysis of rubber flange or burrs , in order to establish in a proposed way technical design specifications for the recovery of material for energy production; starting from the rubber burr, for later application and benefit in the company Croydon Colombia S.A in the city of Bogotá. That is why, through a previous bibliographical review, the energy potential, the importance of the reuse of vulcanized rubber waste and its different forms of recovery are determined. Similarly, thermal degradation processes for energy purposes are defined, along with pyrolysis, to determine the suitability of the proposal. All adjusted to the needs of the company, in which a diagnosis of the burr generation was made and based on it subsequently a characterization of the burr was made as a raw material in a pyrolysis process. In the characterization, the physicochemical parameters of importance for thermal purposes and their influence on the yields of the pyrolysis process were taken into account. Step followed was carried out the experimental process, at the laboratory level, of the process with rubber burr; for which an experimental design was developed where the factors of temperature and type of burr were evaluated. The respective pretreatment of the raw material was also carried out to start the experimental methodology.